2021
DOI: 10.1186/s13287-021-02486-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells derived from juvenile macaques reversed ovarian ageing in elderly macaques

Abstract: Background Female sex hormone secretion and reproductive ability decrease with ageing. Bone marrow mesenchymal stem cells (BMMSCs) have been postulated to play a key role in treating ovarian ageing. Methods We used macaque ovarian ageing models to observe the structural and functional changes after juvenile BMMSC treatment. Moreover, RNA-seq was used to analyse the ovarian transcriptional expression profile and key pathways through which BMMSCs rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The conversion of a pluripotent VSEL with open chromatin into OSCs involves extensive epigenetic changes, and this process is affected by aging. Ovarian aging can be reversed by transplanting MSCs directly into the ovaries ( Tian et al, 2021 ; Wu et al, 2022 ) and by providing a younger niche. Aged ovaries possess rare premeiotic germ cells that can generate oocytes, following transplantation into a young host environment ( Niikura et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of a pluripotent VSEL with open chromatin into OSCs involves extensive epigenetic changes, and this process is affected by aging. Ovarian aging can be reversed by transplanting MSCs directly into the ovaries ( Tian et al, 2021 ; Wu et al, 2022 ) and by providing a younger niche. Aged ovaries possess rare premeiotic germ cells that can generate oocytes, following transplantation into a young host environment ( Niikura et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have multidirectional differentiation potential and immune regulation capability, secreting a variety of bioactive factors and playing important roles in inflammation, tissue damage repair and aging degeneration. In a study of a rhesus monkey aging model [ [10] , [11] , [12] , [13] ], we found that bone marrow MSCs (BMMSCs) derived from infant rhesus monkeys restored the structure and function of aging ovaries by promoting follicular and vascular regeneration, reducing the degree of ovarian fibrosis, and inhibiting apoptosis; improved lung structure and function by reducing fibrosis and inhibiting apoptosis, enhancing the division and proliferation of alveolar type II epithelial cells and improving their antioxidative stress ability; and significantly reversed the expression of age-related proteins in serum. In our previous study, it was also observed that MSCs could improve the structure and function of the thymus in elderly mice [ 14 ], but this observation needed to be confirmed with further studies in nonhuman primates, which are more closely related to humans.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have investigated methods to improve ovarian functions, and the effects of stem cells or exosomes on ovarian functions have been well-documented ( 10 ). For example, human umbilical cord mesenchymal stem cell-derived exosomes can partly delay ovarian aging in female mice ( 11 ).…”
Section: Introductionmentioning
confidence: 99%